NILAI NORMAL KECEPATAN HANTAR SARAF MOTORIK ULNARIS SIKU - Corry Novita Mahama*, Nizar Yamanie**, Fitri Octaviana**, Herqutanto*** (NEURONA, 2011)
INTRODUCTION NERVE CONDUCTION STUDY IS A PART OF ELECTRO DIAGNOSTIC PROCEDURES THAT HAVE BEEN PROVEN USEFUL IN THE EVALUATION OF THE FUNCTION OF THE PERIPHERAL NERVOUS SYSTEM INCLUDING THE ULNAR NERVE THERE ARE PHYSIOLOGICAL AND NON PHYSIOLOGICAL ASPECTS TO THE ULNAR NERVE CONDUCTION VELOCITY THE USE OF ULNAR CONDUCTION VELOCITY MEASUREMENT AS A DIAGNOSTIC PROCEDURE REQUIRES A KNOWLEDGE OF THE RANGE OF VALUES ENCOUNTERED IN HEALTHY INDIVIDUALS